Profil e-marketing mix jasa dan mutu layanan kesehatan - Rizqi Mubarok; Kosasih Kosasih; Vip Paramarta (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Advances in information technology have brought significant changes to healthcare services, particularly in the interactions between hospitals, medical personnel, and patients. Implementing a digital marketing mix (e-marketing mix) is one strategy that can support improving the quality of healthcare services in the digital era. Purpose: To evaluate the implementation of the digital marketing mix and the quality of healthcare services. Method: This study used a quantitative approach with a survey method involving 97 respondents selected using a random sampling technique. The population in this study were patients of the Bima Regency General Hospital who met the inclusion criteria, namely patients who had previously used services at the hospital. Data were collected through questionnaires and analyzed using descriptive analysis and reliability testing with the help of SPSS software. Results: The core elements of the digital marketing mix, including product, place, price, personalization, privacy, customer service, community, and website, received positive reviews from the majority of respondents, with excellent reliability (Cronbach's Alpha = 0.899). Meanwhile, the supporting elements of promotion, security, and sales promotion received relatively lower ratings, although they still demonstrated good reliability (Cronbach's alpha = 0.793). Furthermore, the majority of respondents expressed satisfaction with the quality of healthcare services provided. Conclusion: Implementing core e-marketing mix elements and good service quality can shape positive patient perceptions of hospital services. However, the promotion, security, and sales promotion aspects still require further development. Keywords: Digital Services; E-Marketing Mix; Healthcare Quality; Patient Perception; Patient Satisfaction.